Effect of Structural Design of Silver/Silver Chloride Electrodes on Stability and Response Time and the Implications for Improved Accuracy in pH Measurement - Paul J. Brewer; Richard J. C. Brown (Sensors, 2009)
The response time of thermal electrolytic Ag/AgCl reference electrodes is defined by the porous structure that limits the rate at which traces of any previous solution are diluted by any new solution environment. The electrode stabilisation time when transferred from one electrolyte to another has been shown to change when different structural designs to the conventional sphere of Ag/AgCl are used. Electrodes fabricated with cylindrical architectures of Ag/AgCl have shown improved stability and reach equilibrium faster than spherical electrodes. This work has positive implications for the accuracy and throughput of primary pH measurements made using the Harned cell.